Self-Acceptance Whit Gratitude On New Student Of MA Ma’arif 17 Tarbiyatus Shibyan - Dwi Septiana Khofida Wati; Hadi Ismanto (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2021)
This study aims to determine students' self-acceptance and gratitude. The subject of this research is one of the new students at MA Ma'arif 17 Tarbiyatus Shibyan. This research is a case study using data collection techniques in the form of interviews and assisted by a recording device. Interviews were conducted in an unstructured and semi-structured manner. Observation activities are carried out by observing the phenomena that arise accurately, and analyzing various aspects that arise so as to produce data in accordance with the facts and phenomena that occur in the field. The results of the research from the case study are that gratitude for what each student has has an impact on student self-acceptance.